Validity and reliability of the microsoft kinect to obtain the execution time of the taekwondo `s frontal kick - Flor, C. A. G.; Silvatti, A. P.; Menzl, H. J. K.; Bernardina, G. R. D.; de Souza Vicente, C. M.; Pereira de Andrade, A. G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this study was to verify the validity and reliability of the Microsoft Kinect® as a tool to analyze the time of the frontal kick of the Taekwondo (ap chagui). The volunteers performed 15 repetitions of this kick while the execution time data was been obtained, simultaneity, by the Microsoft Kinect® and the OptiTrack System (golden pattern). In order to verify the reliability of the durations of the kicks we calculated the Intraclass Correlation Coefficient (ICC3,k) between execution times found for each system. The Pearson Correlation was used to test the concurrent validity. The results of ICC and r Pearson presented in this study indicate that the Microsoft Kinect®, associated with a tracking algorithm, could be a feasible tool to evaluate the execution time of the frontal kick of the Taekwondo (ap-chagui).